REPRESENTASI NILAI KESETARAAN GENDER DALAM MATERI PAI DI SEKOLAH MENENGAH DAN KONTRIBUSINYA TERHADAP SDGS 5 - Zulfa; Purwidianto (LPPM STAI Muhammadiyah Probolinggo, 2026)
The representation of gender equality values in Islamic Religious Education materials is crucial to help students understand equitable gender relations. However, there is little research assessing gender representation in IRE textbooks and its relationship with Sustainable Development Goal (SDGs) 5. This study aims to analyze gender equality values in IRE textbooks for secondary schools and explain their role in achieving SDGs5. This study uses content analysis on PAI textbooks for junior high and high school levels. The analysis process includes coding themes, categories of gender representation, and reviewing relevant verses from the Qur'an. The results show bias in gender representation, with a dominance of male roles and limited portrayals of women, especially in the domestic context. There is a discrepancy between the values of equality in Islamic teachings and their presentation in PAI textbooks. In addition, the contribution of PAI to SDGs 5 is not yet clear in the learning materials. In conclusion, there needs to be improvement in gender representation in textbooks and the development of more critical and reflective PAI learning methods to strengthen the contribution of PAI to SDGs 5. The innovation of this research is the empirical analysis of PAI textbooks linked to SDGs 5 achievement indicators.schools.